Role of Education on Socio-Economic Status of Women: Addressing Inequality and Empowering Women through Education (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The reality of women’s lives remains invisible to men and women alike and this invisibility persist at all levels beginning with the family to the nation. The mere fact that “women hold up half the sky” does not appear to give them a position of dignity and equality. True, that over the years women have made great strive too many areas with notable progress in reducing some gender gaps. Yet “afflicted world in which we live is characterized by deeply unequal sharing of the burden of adversities between women and men”.